SIOP-E-BTG and GPOH guidelines for diagnosis and treatment of children and adolescents with low grade glioma - Gnekow, Astrid K.; Kandels, Daniela; Tilburg, Cornelis M. van; Azizi, Amedeo A.; Opocher, Enrico; Stokland, Tore; Driever, Pablo Hernaiz; Meeteren, Antoinette Y. N. Schouten van; Thomale, Ulrich W.; Schuhmann, Martin U.; Czech, Thomas; Goodden, John Robert; et al. (Klinische Pädiatrie, 2019)
Low grade gliomas (LGGs) constitute the largest, yet clinically and (molecular-) histologically heterogeneous group of pediatric brain tumors of WHO grades I and II occurring throughout all pediatric age groups and at all central nervous system (CNS) sites. The tumors are characterized by a slow growth rate and may show periods of growth arrest. Around 40% of all LGG patients can be cured by complete neurosurgical resection and are followed by close observation. In case of relapse, second resection often is possible. Following incomplete resection observation is recommended, as long as there is no radiologic tumor growth and the patient does not suffer from significant, tumor-related symptoms. This also applies to patients with a diagnosis of LGG on the basis of radiological criteria. By contrast, clinical worsening and / or radiologic progression are an indication to treatment with either chemo- or radiotherapy. Overall survival is around 90%, and many patients survive with residual tumor, i. e. they suffer from chronic disease. All patients need comprehensive neuro-oncological care, the principles and details of which are summarized in the current guidelines. These represent standard of care for diagnostic work-up (including neuroimaging and neuropathology), and for therapeutic decisions (including the indications to non-surgical treatment) as well as concepts for neurosurgical intervention, chemotherapy and radiotherapy as well as surveillance and rehabilitation. The current treatment algorithm was compiled by members of the LGG working group of the SIOP-E brain tumor group (SIOP-E-BTG) and is based upon the results of previous European LGG studies and international reports.